Autonomic computing in internet of things for resource management - Ashraf, Qazi Mamoon; Habaebi, Mohamed Hadi; Islam, Md Rafiqul; Tahir, Mohammad (AICIT Korea, 2015)
Internet of Things (IoT) is understood to bring along major research challenges due to the introduction of machine to machine (M2M) applications with no or minimal human supervision. A lot of challenges exist in the scope of resource management due to the high heterogeneity, high complexity and the existence of computational resources at various layers. The theory of autonomic computing provides one approach for dynamic management of such resources. This paper discusses the application of autonomic computing theory in Internet of Things for multi-layered resource management. The issues related to resource management in security are also highlighted. It is found that decision making through autonomic principles can significantly supplement traditional resource management schemes in IoT.